Determination of outdoor recreation potential: case of the city of Bartin and its environs, Turkey - Aytekin, Alper; Kaya, Latif Gürkan (Fresenius Environmental Bulletin, 2009)
This study has been prepared to determine the importance of existing historical, cultural and natural resource values and outdoor recreation areas in the City of Bartın and its environs. Besides, it has been prepared to expose the ecologic and economic potential values of existing recreation resources. Also computer software, which determines the potential of outdoor recreation areas, has been developed to assist the healthy improvement of the city from the recreational point of view. The study takes place within the jurisdiction border of the Bartın Municipality. The study provides information about the definition, classification, etc of the recreation. After natural and cultural characteristics of recreation areas in the city limits have been inspected, existing and potential recreation resources have been determined. Depending on the results of survey, in the frame of protection and usage principles, the recreation resources have been evaluated in order to maintain their best usage, and usage values of these resources have been determined by using the method of Kiemstedt (1967) [27] that has been developed by Altan (1976) [28] and Gülez (1980) [8] for Turkish conditions. Furthermore, computer software has been created in this study, and this developed software puts into practice the method and determines the significance of outdoor recreation potential values quickly and accurately.
Keywords: Outdoor recreation potential; Leisure time; Computer software; Açık hava rekreasyon potansiyeli; Boş zaman; Bilgisayar yazılımı